Single layer versus double layer intestinal anastomoses: a comparative study - Kumar, Ajit; Kumar, Vinod (International Surgery Journal, 2020)
Background: There are still conflicting views regarding suitability of single layer and double layer anastomotic technique. This prospective single blinded randomized comparative study conducted at Rajendra Institute of Medical Sciences to assess various aspects viz. safety, efficacy, duration of hospital stays and chances of perforation in single- and double-layer anastomotic surgery. Methods: 26 patients each in single layer and double layer anastomosis group were included in the study. Single layer intestinal anastomosis was carried using extramucosal technique with 2-0 vicryl suture (round body). Double layer anastomosis was carried out using interrupted 3-0 silk lembert sutures for the outer layer and a continuous 2-0 vicryl for the inner layer. End to end colocolic, end to end ileocolic, end to side ileocolic, end to end ileoileal, side to side ileoileal, end to end jejunoileal and end to end jejunojejunal anastomosis were performed. Each group was compared for anastomotic leak, time required to construct the anastomosis, cost incurred, and length of hospital stay. Results: Findings of the study indicated that single layer is economical in comparison to double layer anastomosis and took significant less time to operate. There was no significant difference in hospital stay of the patients in two groups. There was no anastomotic leak in group-S (single layer) while one (3.8%) patient in group-D (double layer) suffered from anastomotic leak. Conclusions: It was concluded that single layer anastomosis method is beneficial and safe as it required less operative time, suturing material and no leak took place after surgery.